2021
DOI: 10.1017/s0958344021000252
|View full text |Cite
|
Sign up to set email alerts
|

Developing an intelligent tool for computer-assisted formulaic language learning from YouTube videos

Abstract: This paper presents IdiomsTube (https://www.idiomstube.com), the first-ever computer-assisted language learning tool for facilitating the learning of English idiomatic expressions from YouTube videos. The web-based tool is designed to automatically (1) assess the speech rate and lexical difficulty level of any learner-chosen English-captioned YouTube video; (2) generate a range of vocabulary-building and revision tasks (e.g. fill-in-the-blanks, the classic spelling game hangman, pronunciation, flashcards); and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 42 publications
0
9
0
4
Order By: Relevance
“…We also find several dedicated evidence informed L2 learning tools. IdiomsTube (Lin, 2021), for instance, is a computer-assisted learning tool that aims at promoting formulaic language learning from English YouTube videos 14 with captions. To do so, it automatically assesses video difficulty, generates pre-learning activities and tasks, and recommends videos.…”
Section: From Research To Practicementioning
confidence: 99%
See 1 more Smart Citation
“…We also find several dedicated evidence informed L2 learning tools. IdiomsTube (Lin, 2021), for instance, is a computer-assisted learning tool that aims at promoting formulaic language learning from English YouTube videos 14 with captions. To do so, it automatically assesses video difficulty, generates pre-learning activities and tasks, and recommends videos.…”
Section: From Research To Practicementioning
confidence: 99%
“…Research that capitalizes on the affordances of technology is scarce (see Mirzaei et al, 2017 and Lin, 2021 for exceptions). However, a combination of automatic speech recognition and natural language processing techniques could play an important role in making (automatically generated) captions and glossed captions more easily available.…”
Section: Concluding Remarks and Future Directionsmentioning
confidence: 99%
“…Fifthly, it is suggested that more studies be conducted to explore the effects of on-screen texts on the learning of formulaic sequences which comprise idioms, collocations, and other multiword units, as they are pervasive in authentic input and contribute to idiomatic L2 competence (Gholami, 2021a(Gholami, ,b, 2022. Finally, new technologies dealing with different audiovisual input and their effectiveness need to be examined and reported timely so as to contribute to this promising area (e.g., Lin, 2021;Wu et al, 2021). Teaching with audiovisual input may turn out to be the next revolution in L2 vocabulary learning, since the ever-developing multimedia technology offers easy accessibility and simplified manipulation to teachers and learners to meet their requirements whenever and wherever possible.…”
Section: Discussionmentioning
confidence: 99%
“…The result reveals that Youtube videos play a significant role in developing the learners' pronunciation skills. Similarly, the findings of Lin (2022), Mutiarani et al (2022) and Susanti et al (2022) depict the significant role of Youtube to improve language learners' speaking and communication skills.…”
Section:  Introductionmentioning
confidence: 87%